Exploring Paradigm Shift Impacts in Urban Mobility: Autonomous Vehicles and Smart Cities - Medina-Tapia, M (Elsevier B.V., 2018)
Urban mobility is a dynamic system that has had a (slow) natural evolution. Scientists and engineers are currently developing new mobility technologies. A progressive paradigm shift will change everything from the fuel type to the way of driving vehicles. Vehicles will progressively become autonomous and will communicate and cooperate with each other. In the long run, profound changes are expected in mobility as a service. Furthermore, urban areas will have a higher level of development, and cities will likely turn into Smart Cities in which the vehicles will interact with the urban infrastructure. The main objective of this paper is to explore the macroscopic effects of mobility interaction in a radial-circular urban road system for current and future cities (Smart Cities). In the literature, there is documentation of the direct effects of autonomous vehicles, but some indirect effects will cause undesirable impacts such as an increase in demand and more congestion, which change the demand behavior and the urban structure. Finally, this paper exhibits the results of direct and indirect effects calculated through analytical tools (Continuous Approximation Method). In fact, our research shows that if demand increases by about 50%, the current scenario could have the same total cost as the future scenario with autonomous vehicles. Moreover, if the city radius increases by about 33% and the subjective value of time decreases about 20%, the benefits of the autonomous cars will be compensated. Therefore, the paper proves that autonomous vehicles could encourage the urban sprawl in the long run. Finally, Administrations should define transport strategies and policies to control these externalities, because autonomous driving could deteriorate mobility even worse than it is now. © 2018 The Authors. Published by Elsevier Ltd.